Newborn screening and informed consent in a constitutional perspective. The Italian "model" and some knots still to be untied (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Starting from variability analyses in newborn screening systems at international, European and regional levels, this paper focuses on the Italian "model" highlighting some critical issues in a constitutional perspective. The law n. 167 of 2016 and the ministerial decree of 13 October 2016 allowed to achieve uniformity in the national diagnostic offer but their mutual inconsistencies contributed to a regional variability in the management of informed consent/dissent and in the management of the biological material collected. The protection of fundamental rights at stake still requires a constitutionally oriented harmonisation and development of the rules governing the newborn screening national system.
Keywords: Newborn screening; informed consent; informed dissent; constitutional principles; regional variability